Is It Antiphospholipid Syndrome?. (22nd December 2010) - Ditto, Maria Chiara; Antivalle, Marco; Badini, Matteo; Battellino, Michele; Cogliati, Chiara; Sarzi-Puttini, Piercarlo
Abstract : The diagnosis of bacterial endocarditis remains a challenge, as nearly half of cases develop in the absence of preexistent heart disease and known risk factors. Not infrequently, a blunted clinical course at onset can lead to erroneous diagnoses. We present the case of a 47-year-old previously healthy man in which a presumptive diagnosis of antiphospholipid syndrome was made based on the absence of echocardiographically detected heart involvement, a negative blood culture, normal C-reactive protein (CRP) levels, a positive lupus anticoagulant (LAC) test, and evidence of splenic infarcts. The patient eventually developed massive aortic endocarditic involvement, with blood cultures positive for Streptococcus bovis, and was referred for valvular replacement. This case not only reminds us of the diagnostic challenges of bacterial endocarditis, but also underlines the need for a critical application of antiphospholipid syndrome diagnostic criteria.